Profile of Sheep Blood After Administration with CF Amofer - H. Mayulu; . Sunarso; C. I. Sutrisno; . Sumarsono (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
Amoniasi-Fermentation (amofer) technology should be conducted in order to improve the low quality of by product produced from palm oil plantations and mills (palm oil waste) which is used for constituent of feed ingredients in complete feed (CF). This technology also reforms the feed material into edible form. Before broad application, it must be ensured that the feed does not have toxic effects on livestock. This research was peformed to evaluate the effects of amofer palm oil waste-based CF on blood profile and liver function on local sheep. The research was conducted at the Laboratory of Nutrition and Feed Science Diponegoro University Semarang, using 16 local male sheep aged 9 months, weight at 14.82+0.82 kg (CV=5.52%), divided into four groups and put into individual cages. They are given CF containing crude protein (CP) 10.63% (T1), 12.27% (T2), 13.70% (T3) and 15.90% (T4), with Total Digestible Nutrients (TDN) range 61.83–64.21%. Blood samples were taken after the sheep consuming the CF for 37 days. Experimental design used was CRD with 4 replications. Observed variables were the levels of hemoglobin, hematocrit and blood glucose. Data were analyzed using ANOVA of CRD. The average value of blood glucose levels for T1= 80.68 mg/dl, T2=79.08 mg/dl, T3=81.18 mg/dl and T4=73.70 mg/dl. The average value of hemoglobin levels for T1=10.80 g/dl, T2=10.30 g/dl, T3=11.23 g/dl and T4=10.25 g/dl. The average value of hematocrit levels for T1=31.00%, T2=31.00%, T3=33.75% and T4=30%. There was no significant difference among four treatments (p>0.05). The administration CF did not cause hematological disorders which showed by the blood profiles were in normal range, so that suggested the CF was appropriate and safe for local sheep.